2010
DOI: 10.1016/j.jmb.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Determinants of Protein Expression in Prokaryotic Open Reading Frames

Abstract: A quantitative description of the relationship between protein expression levels and open reading frame nucleotide sequences (ORFs) is important for understanding natural systems, designing synthetic systems, and optimizing heterologous expression. Codon identity, mRNA secondary structure, and nucleotide composition within ORFs markedly influence expression levels. Bioinformatic analysis of ORF sequences in 816 bacterial genomes revealed that these features show distinct regional trends. To investigate their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(130 citation statements)
references
References 53 publications
6
122
0
2
Order By: Relevance
“…The degree of secondary structure near the 5′-end of mRNAs has been shown to negatively influence the levels of protein expression (17)(18)(19), which is also observed for the GFP sequence variants that we tested (Fig. S6A).…”
Section: Discussionsupporting
confidence: 64%
“…The degree of secondary structure near the 5′-end of mRNAs has been shown to negatively influence the levels of protein expression (17)(18)(19), which is also observed for the GFP sequence variants that we tested (Fig. S6A).…”
Section: Discussionsupporting
confidence: 64%
“…However, the effect is limited at the extremes; the difference between the weakest and strongest RBSs (an 87-fold increase in translation efficiency) corresponds to only an ∼4.3-fold increase in mRNA. As another example, many groups have found that secondary structure across the 5′ UTR and initial coding sequence can hinder effective translation (14,(43)(44)(45)(46). In our data, we find that the correlation between secondary structure free energy across the UTR/GFP interface is significant (Fig.…”
Section: Resultssupporting
confidence: 56%
“…We do not examine how expression is altered by a gene's amino acid composition and codon use, which are known to have large effects (26,(43)(44)(45)(46). In follow-up work, we explore the influence of these two factors across a matrix of coding sequences, promoters, and RBSs.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2C shows that for linear DNA templates, anti-hIL-23 scFv yields varied between 500 and 950 mg/L, suggesting that single point mutations in the TIR can change the translational efficiency, presumably due to differences in the binding free energy between the ribosomal S1 protein and 5' UTR RNA. As the gene sequence design rules for protein expression are not well understood, 24 this predictable and scalable expression library approach offers the opportunity to rapidly screen DNA synthesized mutants for optimal expression.…”
Section: Resultsmentioning
confidence: 99%